Analisis Fundamental Makro, CSRD Terhadap Nilai Perusahaan dengan Struktur Modal dan Kinerja Keuangan sebagai Variabel Intervening pada Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia - Nurrochmah, Aliatus; Hwihanus (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research aims to analyze the influence of macro fundamental factors, Corporate Social Responsibility Disclosure (CSRD), capital structure, and financial performance on the value of companies in the telecommunications sector listed on the Indonesia Stock Exchange. By using data analysis using SmartPLS. The research results of the nine hypotheses tested, only one hypothesis was accepted, namely that there is a significant influence between capital structure and company value. Meanwhile, another hypothesis shows that CSRD, macro fundamentals and financial performance do not have a significant effect on company value, and no significant effect was found between these variables on capital structure and financial performance. These findings provide implications for telecommunications companies in making strategic decisions regarding capital structure management in increasing company value in a sustainable manner.